Green Infrastructure Development in Urban Areas: Case Studies of Samutsakhon, Krathumbaen and Banphaeo Municipalities in Samut Sakhon Province - Khongouan, Waralak; Khamwachirapithak, Putpunnin (Nakhara : Journal of Environmental Design and Planning, 2021)
Though the development of green infrastructure in parks in Samut Sakhon province has been continuously implemented, there are still no research studies that have explicitly demonstrated the parks’ potential, nor any public opinions toward the development of urban green infrastructure in the parks that would be productive for the planning to efficiently improve and provide urban green infrastructure. As a result, this study had the following objectives: 1) To analyze the potential and networks of urban green infrastructure in parks in Samut Sakhon province, 2) To analyze the satisfaction of using the services and requirements of the urban green infrastructure development in the parks in Samut Sakhon province, and 3) To propose development guidelines in urban green infrastructure for the parks of Samut Sakhon province. The research instruments comprised a questionnaire, and the data were analyzed by using a scalogram. The results found that high-potential parks were not large in size, but they had all the complete components, as well as green infrastructure featured in the attributes of patch, matrix, and mosaic. Nevertheless, the green infrastructure development featured in the attribute of the corridor had disappeared in several sites of the green infrastructure in the parks. Likewise, the green networks of the parks, specifically those in the high-potential category, were not successive by walking. For this reason, the people were mostly satisfied with the convenient accessibility of the parks, but there were the requirements of paving the footpath, improving the landscape, and adding a variety of activities in the parks. Therefore, the development guidelines of urban green infrastructure in the parks should formulate more areas in the attribute of the corridor at the riverside and on the streets, conserve and increase the park areas by allowing public participation in the management, as well as apply urban planning measures to obtain the park area. In addition, a footpath and bike lane should be safely constructed in the high-potential parks. Simultaneously, the landscape should be adjusted in the low- and moderate-potential parks by launching pilot projects in the parks of the governmental agencies.